Social responsibility of kindergarten teachers Eligibility and Government (Comparative Study) - Kalthoom Abd Aon كلثوم عبد عون (College of Education for Women, 2018)
The present research aims to identify the social responsibility of the kindergarten teachers of the civil and governmental schools (comparative study)? For the purpose of achieving the objectives of the research, the following formulas were formulated: - Are there statistically significant differences at the level of (0.05) among the kindergarten teachers in the social responsibility scale?  The current research was limited to kindergarten teachers (governmental and non-governmental) in the Directorate General of Education Baghdad Rusafa / Second. The main research sample consisted of (100) teachers, (50) teachers from government kindergartens and (50) female kindergarten teachers. To achieve the research objectives, the researcher constructed a social responsibility measure consisting of (40) Ali often, apply to me sometimes, do not apply to). After making the appropriate adjustments in the light of the observations of the experts and arbitrators, and verify the sincerity and stability, and the strength of excellence, and the relationship of the paragraph in the overall degree. The researcher reached the following results: 1- The results indicate that kindergarten teachers are generally socially responsible. The teachers of state kindergartens are superior to the social responsibility of female kindergarten teachers